The Universal Journalist - Randall, David (Pluto Press, 2021)
This is the only 'how to' book on journalism written by writers and editors who have operated at the top level in national news. It has long been the go-to book of advice for young reporters This edition includes a chapter on social media and is extensively updated throughout, with new content from Jemma Crew, an award-winning national news journalist. The book emphasises that good journalism must involve the acquisition of a range of skills that will empower trainees to operate in an industry where ownership, technology and information are constantly changing. This handbook includes tips and tricks learned from working at the very top of the business, and is an invaluable guide to the 'universals' of good journalistic practice for professional and trainee journalists worldwide.